1951
DOI: 10.1063/1.1748245
|View full text |Cite
|
Sign up to set email alerts
|

The Bonding of Trihalide and Bifluoride Ions by the Molecular Orbital Method

Abstract: A simple molecular orbital treatment is presented to explain the bonding in trihalide ions, X3−, XY2−, and XYZ−, and bifluoride ion, HF2−. The M.O.'s are formed from linear combinations of npσ halogen orbitals, and the 1s hydrogen orbital and stable bonding M.O.'s are obtained without the introduction of higher atomic orbitals. Applications are suggested in prediction of other stable species and low energy reaction intermediates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
301
1
10

Year Published

1971
1971
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 644 publications
(329 citation statements)
references
References 11 publications
17
301
1
10
Order By: Relevance
“…We showed earlier the various diborane phases considered. Of these, we took the β form to higher pressure and compared its enthalpy to those of extended arrays of molecular trimer, tetramer, hexamer, and infinite chain of BH 3 . The optimized structures we found (at 40 GPa) are shown in Figure 5, and their enthalpies as a function of pressure in Figure 6.…”
Section: Journal Of the American Chemical Societymentioning
confidence: 99%
See 1 more Smart Citation
“…We showed earlier the various diborane phases considered. Of these, we took the β form to higher pressure and compared its enthalpy to those of extended arrays of molecular trimer, tetramer, hexamer, and infinite chain of BH 3 . The optimized structures we found (at 40 GPa) are shown in Figure 5, and their enthalpies as a function of pressure in Figure 6.…”
Section: Journal Of the American Chemical Societymentioning
confidence: 99%
“…XXXX, XXX, XXX−XXX trimer, has not been unambiguously characterized in experiments. Fridmann and Fehlner 44 observed the formation of a triborane product, suggested to be B 3 H 9 , in the reaction of BH 3 and B 2 H 6 . Theoretical calculations 45 suggested that the step II is associated with activation and reaction enthalpies (at 400 K) of approximately 14 and −5 kcal/mol, respectively.…”
Section: Journal Of the American Chemical Societymentioning
confidence: 99%
“…Oxygen with a ground-state atomic configuration of 1s 2 2s 2 2p x 2 2p y 1 2p z 1 has a nominal valence of two and forms stable compounds such as H 2 O and F 2 O (as well as the radicals OH and OF, which have one unsatisfied valence). However, main group elements beyond the first row regularly form stable molecules that exceed their nominal valence, e.g., sulfur, which is in the same group as oxygen, forms SF 4 and SF 6 in which sulfur has a valence of 4 and 6, respectively. Musher 1 and Schleyer 2 coined the terms "hypervalent" and "hypercoordinated," respectively, to denote molecules where the nominal valence of the atoms is exceeded.…”
Section: Introductionmentioning
confidence: 99%
“…Musher 1 and Schleyer 2 coined the terms "hypervalent" and "hypercoordinated," respectively, to denote molecules where the nominal valence of the atoms is exceeded. Several models have been advanced to rationalize the existence of hypervalent species, the most widely accepted today being the RundlePimentel 3-center, 4-electron (3c-4e) model, which uses basic molecular orbital arguments to rationalize the existence of hypervalent species 3,4 although this rationalization is not without its inconsistencies. 5 Previous studies of the halides of the second row, late p-block elements, by our group have shown that hypervalent or hypercoordinated molecules possess a previously unrecognized type of bond, a recoupled pair bond.…”
Section: Introductionmentioning
confidence: 99%
“…The bonding•in the hydrogen dichloride species can be treated as a three center bond formed from combination of the hydrogen ls orbital and chlorine 3P orbitals [7].…”
mentioning
confidence: 99%